“Houses. Cats. Cars. Trees. Me”: Outward and Inward Journeys in Joe Brainard’s Collage Travelogues - Drąg, Wojciech (Studia Anglica Posnaniensia, 2021)
This article examines two brief travelogues by the American writer and visual artist Joe Brainard (1942–1994) as formally unique fusions of the travel journal and literary collage, in which the experience of travel becomes a catalyst for introspection. “Wednesday, July 7th, 1971 (A Greyhound Bus Trip)” is a record of a bus journey that Brainard made in the summer of 1971, from the Port Authority Bus Terminal in New York City to Montpelier, Vermont, while “Washington D.C. Journal 1972” is a diary of a three-day car trip to the capital, taken with Brainard’s oldest friend (and future biographer), the New York School poet Ron Padgett and his wife and son. In both texts, a description of the particulars of the trip is combined with meditation about the author’s life and career. After introducing the structure of the travelogues, the article demonstrates their formal indebtedness to literary collage, which relies on fragmentation, heterogeneity, parataxis, and the use of appropriated content. What follows is an analysis of the texts’ oscillation between an account of external stimuli and a record of Brainard’s train of thought. It is argued that, gradually, the inward journey becomes more important than the outward, leading the author towards pushing the boundaries of his candour (in “Wednesday”) and towards an artistic self-assessment (in “Washington”). The article interprets those works as a manifestation of twentieth-century travel writing’s turn towards self-reflectiveness and concludes by considering the relationship between fragmentary, collage-like form and introspective content in the texts at hand, as well as in Brainard’s entire artistic output.